Using Personal Handheld Computing Devices for Personalizing Healthcare - Gogia, S. B.; Maeder, A.; Meher, S.; Mars, M.; Hartvigsen, G.; Kuthiala, A. (Yearbook of Medical Informatics, 2012)
Telehealth has an increasing role in future healthcare. This paper seeks to define and understand recent advances in provision of tele-healthcare through use of personal handheld computing devices, and suggests how such personalized solutions offer further opportunities for progress.We considered the current status of personal handheld computing devices for personalizing healthcare, through review of examples in the literature and web sources.We have identified the following four generic roles for personal handheld computing devices in personalized healthcare: educational, social networking and games, monitoring with notifications/reminders, and online/offline tele-consultations. We discuss examples of these in two settings: healthcare facilities and patient home.Advances in latest handheld computing devices have made tele-healthcare more personalized and increasingly possible even in the absence of the care provider.
Keywords: Personal handheld computing devices; personalizing healthcare; tele-healthcare; telehealth